Structural Manipulation of Phase Transitions by Self‐Induced Strain in Geometrically Confined Thin Films. (20th September 2020) - Kalcheim, Yoav; Adda, Coline; Salev, Pavel; Lee, Min‐Han; Ghazikhanian, Nareg; Vargas, Nicolás M.; del Valle, Javier; Schuller, Ivan K.
Abstract: Strain engineering is a well‐known method often used to tune material properties in thin films. The most studied sources of strain are lattice mismatch and differential thermal contraction between the substrate and film. However, in materials which undergo a structural phase transition (SPT), a third and often overlooked source of strain may play a very significant role. If the substrate confines the area of the film, the SPT may induce stress which changes the evolution of the transition. This is a 2D analog of the isochoric phase transition between water and ice, where the freezing point drops below 0 °C. To illustrate this, the prototypical Mott insulator V2 O3 which has an SPT coupled to a metal–insulator transition is used to show how self‐induced strain can drastically alter structural and electronic properties. This effect provides an elegant approach for mapping the phase diagram of the SPT and the transitions coupled to it. Moreover, the magnitude of self‐straining is tunable by modifying the substrate morphology. This effect may be important for numerous materials which exhibit an SPT and are subjected to geometrical constraints. Abstract : The trajectory of phase transitions can be controlled by confining the material volume as temperature is changed. Here, a 2D analog of this effect is achieved in thin films using the substrate to constrain their area. The buildup of self‐induced stress allows control of the structural transition in the archetypal Mott insulator V2 O3 with drastic effects on electronic properties.